Multicriteria Decision Evaluation of Adaptation Strategies for Vulnerable Coastal Communities - Mostofi Camare, Hooman (Université d'Ottawa / University of Ottawa, 2011)
According to the IPCC (2007) fourth assessment report, small islands and coastal communities have a set of characteristics that makes them very vulnerable to climate change impacts, mainly sea-level rise and storm surges. Coastal hazards including inundation, salinisation of the water supply, and erosion threaten vital infrastructure that support coastal communities. Although Canada has the longest coastline in the world, little work has been done on impacts of climate change and adaptation to these impacts in the Canadian coastal zones. This research is part of an International Community-University Research Alliance (ICURA) C-Change, project to develop a multicriteria decision evaluation and support for the systems analysis of adaptation options for coastal communities toward adapting to environmental changes. This study estimates the vulnerability of coastal communities with respect to their environmental, economic, social, and cultural dimensions. It also applies a group version of the Analytical Hierarchy Process for identifying decisions that various stakeholders make on suggested adaptation strategies. This study develops a methodological framework that is applicable to various coastal and small island contexts. The application of the proposed framework is further discussed in a case study conducted on the communities of Charlottetown, Prince Edward Island (PEI), and Little Anse on Isle Madame, Nova Scotia. Specifically, the state of the Little Anse breakwater is analyzed and new adaptation options are presented and evaluated. This research has illustrated and applied a process of decision evaluation and support that explicitly engages multiple participants and critieria in complex problems situations involving environmental change in coastal communities.
Keywords: MCDM; Vulnerability; Coastal Communities; Adaptation; Group Decision Making